Shariah Governance, Leverage, And Their Impact on Islamic Corporate Social Responsibility in Sharia Banking in Indonesia - Yani Suryani; Saparuddin Siregar; Nurlaila Nurlaila (International Journal Ihya' 'Ulum al-Din, 2024)
This research aims to test and analyze the influence of Shariah Governance and Leverage on Islamic Corporate Social Responsibility. The population in this study consisted of 14 Sharia Commercial Banks in Indonesia, with a sample of 10 Sharia Commercial Banks obtained using the purposive sampling method. The research methodology used is quantitative with the analytical tool used is panel data regression with Eviews 10 software. Research findings show that Sharia Governance significantly affects Islamic Corporate Social Responsibility (CSR). The implementation of sharia governance expands the disclosure of Islamic Corporate Social Responsibility (ICSR). However, Leverage does not affect Islamic Corporate Social Responsibility. The lack of leverage impact as measured by the total debt-to equity ratio is caused by Islamic banking, both with high and low levels of leverage, still revealing Islamic Corporate Social Responsibility as measured by the Islamic Social Reporting Index (SRI). as a means of fulfilling information needs for customers. It represents man's accountability to God and, aims to gain legitimacy from God as an ultimate goal.